Water-soluble vidarabine derivatives alleviate catecholamine-induced heart failure and arrhythmia without impairing cardiac function in mice - Kenji Suita; Yoshio Hayakawa; Yujiro Hoshino; Wenqian Cai; Reiko Kurotani; Yoshiki Ohnuki; Yasumasa Mototani; Yoshihiro Ishikawa; Satoshi Okumura (PLoS ONE, 2025)
The worldwide standard guideline for treating heart failure (HF) is inhibition of the patients’ chronically enhanced sympathetic nervous system activity. However, despite gains in the treatment of HF with angiotensin and β-adrenergic receptor (β-AR) blockers, some patients do not tolerate β-AR blocking therapy to inhibit cardiac function and contract the respiratory tract. One approach to address this would be adenylyl cyclase (AC) isoform-specific therapy. Indeed, we have demonstrated that vidarabine’s selective AC-inhibitory effect in the heart can inhibit the development of HF and arrhythmia without suppressing cardiac function in mice. However, the potential usefulness of vidarabine is limited by its poor solubility, which requires continuous infusion in a large volume of intravenous fluid over a prolonged period. Here, in order to overcome this problem, we aimed to develop vidarabine derivatives with increased solubility and maintained activity. We synthesized derivatives substituted with a (dimethylamino)acetyl group at the 2’-, 3’- or 5’- position of the arabinose ring (V2E, V3E and V5E, respectively) and evaluated their activity in vitro and in vivo. V2E, V3E and V5E all possess greater water solubility than vidarabine and their inhibitory effect on cardiac AC activity is comparable to that of vidarabine. Furthermore, V2E, V3E and V5E ameliorated the development of HF and reduced the susceptibility to atrial fibrillation in a mouse model.